Transcriptome-wide association study and eQTL analysis to assess the genetic basis of bulb-yield traits in garlic (Allium sativum) - Siyuan Zhu; Xiaojun Chen; Xia Liu; Jian Zhao; Touming Liu (BMC Genomics, 2019)
Abstract Background Garlic bulbs are abnormal expanding axillary buds that are rarely found among vascular plants. Bulb-yield is one of the valuable agronomic traits of garlic. However, due to the large genome size and a strictly asexual life cycle in the cultivars, the genetic basis of the yield traits are poorly understood in garlic. Results In the present study, we carried out an association mapping for three yield traits of garlic bulbs: bulb weight (BW), diameter (BD), and the number of garlic cloves (CN), using the recently proposed transcriptome-referenced association study. In total 25, 2, and 30 single nucleotide polymorphisms (SNPs), were identified in the transcripts to be associated with BW, BD, and CN traits, respectively. Of the transcripts with associated SNPs, the expression of 17 of them showed a significant correlation with the corresponding traits in the population, suggesting their relation to bulbs yield traits. Six transcripts were long non-coding RNAs (lncRNAs), and the others encode proteins involved mainly in carbohydrate metabolism, transcription regulation, cytokinin activity, protein degradation, etc. In addition, expression quantitative trait locus (eQTL) and expression correlation analysis have revealed that seven CN-related transcripts displayed interrelation, constituting two potential pathways. Conclusion This study provides novel insights into the genetic basis of the yield traits in garlic bulbs, and the identification of trait-associated SNPs/transcripts provides a basis for improving the bulb yield in garlic breeding.